Identification and Histological Observation of Endophytic Fungi Isolated from Medicinal Plant, Physalis angulata L. - Utami Sri Hastuti; Sulisetijono Sulisetijono; Dwi Rahmawati; Ria Yustika Sari; Sugi Hartono; Chomisatut Thoyibah; Fitria Maulita; Faiza Nur Imawati Ningsih; Siti Hartina Pratiwi (Bogor Agricultural University, Indonesia, 2021)
Some endophytic fungi species live in medicinal plant tissue and does not make any damage, but live in symbiotic mutualism relationship with the host plant. This research was done to: 1) identify the endophytic fungi species isolated from P. angulata leaf, twig, and stem bark tissues, 2) determine the endophytic fungi colonization in the P. angulata plant tissue by histologic observation. The endophytic fungi was isolated from healthy P. angulata plant parts, then inoculated on Potato Dextrose Agar medium and incubated in 27°C for 7-14 days. Each endophytic fungi isolates were identified. The histologic observation was done by microscopic observation to determine the endophytic fungi position in the plant tissue. The conclusion are: 1) seven endophytic fungi species were found: Penicillium verrucosum, Colletotrichum alienum, Fusarium subglutinans, Aspergillus nidulans, Mycelia sterilia 1, Mycelia sterilia 2, and Rhizoctonia sp.; 2) the endophytic fungi micelium was found on the leaf epidermis cell wall, on the twig epidermis cell wall, and parenchyma cell wall, on the stem bark epidermis cell wall. The suggestion of the study: it is need to make the next research about secondary metabolites content produced by endophytic fungi species isolated from P. angulata and their antimicrobial activity.